Decrease of Risk of Developing Symptoms of OAB in Elderly Men and Women Treated with Loop Diuretic for Hypertensive Disease Using Solifenacin - V. Kosilov, Kirill; A. Loparev, Sergay; A. Ivanovskaya, Marina; V. Kosilova, Liliya (Current Aging Science, 2014)
Objectives: Materials and Methods: Randomized double blind longitudinal study was performed from December 1, 2012 to June 15, 2013 in urological ward of gerontological hospital (Vladivostok city, Russian Federation). 378 men and women over 65 (average age: 69.8 (7.2)), who suffered from stage 1 (initial) hypertension, had participated in this study. During the treatment all patients, except for those who were assigned to the control group, received Loop Diuretic Furosemide dosed at 20-30 mg per day and Solifenacin dosed at 5 mg per day (First comparison group) and 10 mg per day (Second comparison group). Functional performance of lower urinary tract (LUT) at enrollment and at the end of the treatment was evaluated using ICIQ-SF questionnaires. During the whole period of treatment patients were keeping bladder diaries where records on frequency and volume of daily urinations, episodes of urgency (EU), episodes of incontinence (EI) and other symptoms were kept. Result: Comparison of data obtained from control group (7.2%), group of the patients treated with Furosemide and standard- dosed (11.1%) and low-dosed (16.2%) Solifenacin allows to draw conclusion on the absence of significant differences in number of patients with symptoms of OAB between these groups (p ≥ 0.05). At the same time percentage of patients with symptoms of OAB in the group treated only with Furosemide was significantly different from three other groups (p ≤ 0.05) and reached 46.1%. Conclusion: Risk of developing symptoms of OAB in elderly patients, whose hypertensive disease has been treated with loop diuretic for a long period of time, decreases significantly, provided antimuscarinic drug Solifencin is administered at the same time. Administration of low dosed Solifenacin is sufficient for significant decrease in risk of developing symptoms of overactive bladder.
Keywords: furosemide